Comparison of the clinical impact of endoscopic ultrasound-guided choledochoduodenostomy and hepaticogastrostomy for bile duct obstruction with duodenal obstruction - Ogura, Takeshi; Chiba, Yasutaka; Masuda, Daisuke; Kitano, Masayuki; Sano, Tatsushi; Saori, Onda; Yamamoto, Kazuhiro; Imaoka, Hiroshi; Imoto, Akira; Takeuchi, Toshihisa; Fukunishi, Shinya; Higuchi, Kazuhide (Endoscopy, 2016)
Background and study aim: To date, only a few reports with small numbers of patients have described double stenting (biliary and duodenal), in particular endoscopic ultrasound (EUS)-guided biliary drainage, for patients with obstructive jaundice. In addition, no reports have sought to determine which EUS-guided biliary drainage route has better outcomes. The aim of the current study was to investigate adverse events and stent patency in patients who underwent EUS-guided biliary drainage and duodenal stenting.Patients and methods: Patients who were admitted to the Osaka Medical College with obstructive jaundice caused by lower biliary obstruction and duodenal obstruction due to malignant tumor between June 2012 and April 2014 were retrospectively enrolled in the study.Results: A total of 39 patients were enrolled in the study; 13 underwent EUS-guided choledochoduodenostomy (EUS-CDS), and 26 underwent EUS-guided hepaticogastrostomy (EUS-HGS). Adjusted analyses for covariates using propensity scores showed that the EUS-HGS group had significantly longer stent patency than the EUS-CDS group (duodenal stent patency: median 113 vs. 34 days; hazard ratio [HR] 0.415, 95 % confidence interval [CI] 0.175 – 0.984; P = 0.046; biliary stent patency: median 133 vs. 37 days; HR 0.391, 95 %CI 0.156 – 0.981; P = 0.045). On logistic regression analysis, only EUS-CDS was associated with adverse events, in particular reflux cholangitis (OR 10.285, 95 %CI 1.686 – 62.733; P = 0.012). Conclusion: In cases of obstructive jaundice with duodenal obstruction, EUS-HGS may be better than EUS-CDS, with longer stent patency and fewer adverse events.